Pengaruh panjang tes dan ukuran sampel terhadap kekerasan estimasi parameter pada teori respon butir (Item Response Theory) - Sukirno DS, Sukirno DS (Jurnal Cakrawala Pendidikan, 2006)
Developing fair and objective test had been developed in many ways, but hey would solve huge educational problem. Simulation study conducted by Hableton and Cook, inspired ths study to looked for evidence the effect of test length and sample size on robustness of item parameters estimation. This article gave more evidences in describing the effect of tst length and sample size on robustness of item parameters estimationin norm reference evaluation of item response theory.Hypothecical data used in this study was generated by DGEN applicatioan program. Test length was modeled in 15 and 55 items that represent short and long test form. The sample size effect was tested by three different sample sizee, 271, 605, and 1.999 to estimate 1,2,and 3 parameter according to the rule of thumb.